2017
DOI: 10.18203/2320-1770.ijrcog20174093
|View full text |Cite
|
Sign up to set email alerts
|

Study of reproductive health problems in adolescent girls at ESIC PGIMSR, MGM Hospital, Parel, Mumbai: a retrospective study

Abstract: Background: There are almost 200 million adolescents in India. It is estimated that the adolescent group constitutes about one fifth of India’s population and it is estimated that this age group will grow to over 214 million by 2020. The period of adolescence for a girl is a period of physical and psychological preparation for safe motherhood. Several factors contribute to the adolescents' growth. A vast majority of adolescent girls in India are suffering from menstrual problems, reproductive morbidities and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…The current analysis also found that among SRH problems, white discharge (12.89%), ovarian cyst (5.63%), and bleeding and pain (3.54%) were major issues that were reported. A similar observation was found in a hospital-based retrospective study among adolescents (10-19 years), that white discharge was the most common reproductive health problem among adolescent girls [20]. A significant reduction in counselling for SRH problems (<0.001), menstruation-related problems (<0.001), nutrition (<0.005), and other health problems (<0.001) from the pre-COVID-19 period to the post-COVID-19 period was observed.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The current analysis also found that among SRH problems, white discharge (12.89%), ovarian cyst (5.63%), and bleeding and pain (3.54%) were major issues that were reported. A similar observation was found in a hospital-based retrospective study among adolescents (10-19 years), that white discharge was the most common reproductive health problem among adolescent girls [20]. A significant reduction in counselling for SRH problems (<0.001), menstruation-related problems (<0.001), nutrition (<0.005), and other health problems (<0.001) from the pre-COVID-19 period to the post-COVID-19 period was observed.…”
Section: Discussionsupporting
confidence: 84%
“…Physiological and anthropometric characteristics such as height, weight, blood pressure, and BMI from 2018-2022 (up to march) are shown in Table 2. Analysis shows that mean height and weight were high among young adults (20)(21)(22)(23)(24) across the observation years. The overall mean height among 20-24 years was (152.58 ± 3.34) and weight (49.79 ± 6.99), respectively.…”
Section: Physiological and Anthropometric Characteristics Of The Bene...mentioning
confidence: 99%
“…In study by Samarth S et al 9.86% had menorrhagia, 11.52% girls had evidence of polycystic ovaries.7Study by Gedam JK had most common menstrual problems being dysmenorrhea and primary amenorrhea in 1.57% of cases similar to our study. 8 In our study anaemia was seen in 40% of girls, 17 girls had hemoglobin % less than 7g%. Serum TSH was normal in 89% of girls.…”
Section: Discussionsupporting
confidence: 50%
“…Anaemia was observed in 57.84% of girls in study by Gedam JK. 8 Menstrual abnormalities are the most common problems of adolescent girls. 3,[9][10][11][12] Thaker RV et al, study had common menstrual problem being dysmenorrhea in 52.9% of cases similar to our study followed by menstrual irregularities.…”
Section: Discussionmentioning
confidence: 99%